2020
DOI: 10.3390/nano10091884
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Cathodes for Electrochemical Reduction of CO2: From Macro- to Nano-Engineering

Abstract: Rising anthropogenic CO2 emissions and their climate warming effects have triggered a global response in research and development to reduce the emissions of this harmful greenhouse gas. The use of CO2 as a feedstock for the production of value-added fuels and chemicals is a promising pathway for development of renewable energy storage and reduction of carbon emissions. Electrochemical CO2 conversion offers a promising route for value-added products. Considerable challenges still remain, limiting this technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 284 publications
0
19
0
Order By: Relevance
“…Although carbon dioxide reduction is highly studied under various conditions, many of them considered herein, the electrochemical CO 2 RR presents many advantages, which were previously discussed for conventional catalytic processes; however, the simplicity of the reaction is one additional gain of the process. Thus, the anodic reaction is the oxygen evolution reaction (OER), [150] while the cathodic counterpart takes the general form: [151] truexCO2+nH++ne-product+yH2normalO …”
Section: Electrochemical Co2 Reduction Reaction (Co2rr) Rhenium Bipyridine‐based Catalystsmentioning
confidence: 99%
“…Although carbon dioxide reduction is highly studied under various conditions, many of them considered herein, the electrochemical CO 2 RR presents many advantages, which were previously discussed for conventional catalytic processes; however, the simplicity of the reaction is one additional gain of the process. Thus, the anodic reaction is the oxygen evolution reaction (OER), [150] while the cathodic counterpart takes the general form: [151] truexCO2+nH++ne-product+yH2normalO …”
Section: Electrochemical Co2 Reduction Reaction (Co2rr) Rhenium Bipyridine‐based Catalystsmentioning
confidence: 99%
“…Owing to the weak interaction between h-BN and Cu, the free-energy change of HCOO* is relatively positive (0.57 eV, Figure 9k), which leads to a high CO formation potential. [185,217] Recently, the ability of C-doped and linear defect-embedded BN nanoribbons (BNNRs) to electrocatalyze the CO 2 reduction has been predicted. [76] It has been shown that C-doped Z-type and armchair BNNRs promote the selective conversion of CO 2 to CH 4 because of their strong binding to CO intermediates.…”
Section: Co 2 Electroreductionmentioning
confidence: 99%
“…Hydrogenating CO 2 into fuel molecules reduces both the greenhouse gas emissions and dependence on nonrenewable energy sources. The electrocatalytic reduction of CO 2 is of great significance, [177,217] but its experimental exploration using BN-based nanomaterials is relatively late and has only been reported recently. It was found that h-BN with defects prepared by ball milling could effectively activate CO 2 molecules for hydrogenation.…”
Section: Electrochemical Co 2 Reductionmentioning
confidence: 99%
“…The previous state-of-the-art review articles [ 84 , 110 , 111 , 112 , 113 , 114 , 115 ] have discussed ECO 2 RR more extensively. The ECO 2 RR using cobalt-based materials has gained considerable interest.…”
Section: Introductionmentioning
confidence: 99%